Basal cell carcinoma in oculo-cutaneous albinism - Kumar, Ajay; Chauhan, Ashish; Kashyap, Subhash (International Journal of Research in Medical Sciences, 2017)
The basal cell carcinoma is the most common skin tumour especially affecting the white individuals worldwide. The exact incidence of basal cell carcinoma is not known from India but non melanoma skin cancers comprises about 1-2% of cutaneous tumour in India. The most common skin tumour is squamous cell carcinoma in albinism and the incidence of basal cell carcinoma is less. Hereby, we report a peculiar case of basal cell carcinoma in albinism to highlights the importance of early recognition and diagnosis of suspected lesions by performing histopathological examination in unusual circumstances.